AN ANALYSIS OF STUDENTSâ MOTIVATION IN STUDYING ENGLISH (A SURVEY STUDY AT UIN AR-RANIRY BANDA ACEH) - Fachraini, Siti (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
Motivation is a key concept to be success in learning. Student who has high motivation would do the best in learning even though the materials were felt difficult. On the contrary, student who has low motivation would get bored and be indifferent in learning even though the materials given were so easy. In line with this, this study tried to investigate studentsâ motivation in learning English, whether they had intrinsic or extrinsic motivation. The study was conducted at English Department of Islamic State University (UIN) Ar-Raniry Banda Aceh. The sample of this study was 142 English students from first, third, fifth and seventh semesters. This study was a survey method and the technique sampling used in this study was random sampling. Furthermore, the instrument used to collect the data is questionnaire. The questionnaire consists of 10 questions in which question 1-5 are questions for intrinsic motivation and question 6-7 are questions for extrinsic motivation. The result of this study shows that the total mean score of intrinsic motivation is higher than the total mean score of extrinsic motivation 4.08 Ë 3.21. It means that English students at UIN Ar-Raniry had higher intrinsic motivation than extrinsic motivation in learning English. In other words, the motivation to learn English that comes from inside students was bigger than the motivation comes from outside students.Keywords: Motivation, English Students